Språk som tema och stoff i Katarina Frostensons diktning - Skalska, Katarzyna (Folia Scandinavica Posnaniensia, 2007)
Language plays a very important role in Katarina Frostenson’s works, being not only the stuff, but also one of the leading subjects. Her literary production is strongly metapoetical and metalinguistic. Frostenson’s views on language have much in common with poststructuralism and deconstruction when she maintains that language is insufficient to describe the world and that consequently, the world is falsified by language. However, contrary to poststructuralists and postmodernists for whom, actually, nothing exists beyond the text, she believes that beyond language there is something like an objective reality, some kind of truth, and what’s more, she believes that it is possible to describe this reality if one can find a suitable language. In her works she tries to seek such a language, for example by going back to the primitive - both childish and archaic - kind of language. This article deals both with Frostenson’s views on language as expressed in her texts, and with how, in consequence, she treats and uses the language in practice.